Emerging challenges and sustainability of industry 4.0 Era in the Malaysian construction industry - Moshood, Taofeeq Durojaye; Adeleke, A. Q.; Nawanir, Gusman; Ajibike, W. A.; Shittu, Rukayat A. (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Today's businesses are challenging what to call a new technological change. Technological advancements are going towards more enhanced internet-based method resolutions. This step is usually pointed to being Industry 4.0 and is supposed to hold the potential for new adaptable, independent products able to manage themselves. By modern technologies, nevertheless, there is additional demand for new skills and qualification demands on the workforce in the construction industry. Moreover, manufacturers or construction companies of today usually have obstacles with hiring newly qualified workers, particularly the younger one. Construction companies are looking to achieve Industry 4.0 would consequently have to maintain the development and education of existing workers while including attracting new workers. The paper objects are to explain what modifications that help achieve a sustainable of industry 4.0 in the construction industry, efficient and recognizing potential developments, understanding hazards connected with economics and supporting the simulation improvement.